Protecting the Right to Village Existence in Indonesia’s National Strategic Projects: Normative Gaps in Village Dissolution, Land Acquisition, and Administrative Safeguards - Bayu Nando Prayoga; Istilam Istilam; Shinta Hadiyantina (IJBLE Scientific Publications Community Inc., 2026)
This article examines the legal implications of village dissolution arising from Indonesia’s National Strategic Projects (Proyek Strategis Nasional, PSN) and assesses whether existing legal instruments adequately protect the right to village existence. The analysis is motivated by the tension between accelerated infrastructure development and constitutional commitments to village autonomy, legal certainty, public participation, and protection of collective community rights. Using normative legal research, the article applies statutory, conceptual, historical, and case-based approaches to the Village Law, the Government Administration Law, the Land Acquisition Law, Government Regulation No. 42 of 2021, Presidential Regulation No. 109 of 2020, and Minister of Home Affairs Regulation No. 1 of 2017. The article argues that PSN regulations facilitate project acceleration, land acquisition, and spatial reclassification, but do not create a clear, rights-sensitive mechanism for altering or extinguishing village legal status. This produces a normative gap: land may be acquired for public interest projects while the subsequent status of village territory, assets, governance participation, customary identity, and collective administrative rights remains legally underprotected. The article further shows that merger, subdivision, and dissolution procedures can be used administratively to neutralize village resistance, especially where customary communities lack formal recognition. It concludes that village dissolution caused by PSN should not be treated as a mere bureaucratic consequence of land acquisition, but as a constitutional event affecting legal identity, social memory, and local self-government. The article recommends mandatory village deliberation, meaningful public consultation, free, prior, and informed consent for customary communities, independent legality review, and explicit statutory safeguards for village existence in the PSN regime